2004
DOI: 10.1143/jjap.43.l1362
|View full text |Cite
|
Sign up to set email alerts
|

Highly Moisture-Resistive SiNxFilms Prepared by Catalytic Chemical Vapor Deposition

Abstract: Silicon nitride (SiN x ) films on Si and poly(ethylene terephthalate) (PET) substrates were prepared at approximately 150 C by catalytic chemical vapor deposition (Cat-CVD), using a SiH 4 /NH 3 gas mixture. A water vapor transmission rate as low as 0.2 g/m 2 day and an O 2 gas transmission rate of 0.6 cm 3 /m 2 day were achieved for a stoichiometric Si 3 N 4 film of 77 nm thickness. Although these transmission rates depended on N/Si ratio, no optical absorption was observed under preferable deposition conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 7 publications
(7 reference statements)
0
19
1
Order By: Relevance
“…The deposition rate achieved in this study is more than two orders of magnitude higher than those obtained by other methods [13][14][15][16][17][18][19]. However, the BHF etching rate of the sample with the highest Si-N bond density (28 nm/min) shown in Fig.…”
Section: Film Stabilitycontrasting
confidence: 55%
See 1 more Smart Citation
“…The deposition rate achieved in this study is more than two orders of magnitude higher than those obtained by other methods [13][14][15][16][17][18][19]. However, the BHF etching rate of the sample with the highest Si-N bond density (28 nm/min) shown in Fig.…”
Section: Film Stabilitycontrasting
confidence: 55%
“…Besides, lowering substrate temperature leads to a further deterioration of film quality due to the increase in film porosity [11,12]. As for the improvement of film density at low temperatures, great efforts have been made [13][14][15][16], and other effective ways, such as hot-wire (catalytic) CVD [17,18] and the use of expanding thermal plasma [19], have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon nitride (SiN x ) films prepared by catalytic chemical vapor deposition (Cat-CVD) method, which can be performed under 100°C without thermal damage to OLEDs, are expected to act as protection films for OLEDs due to the high film density [3][4][5][6]. However, moisture and oxygen can reach organic layers through cracks penetrating the SiN x films caused by roughness of underlying organic films or electrodes, which generates dark spots in OLEDs [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that high-quality SiN x films can be obtained below 200 -C using a SiH 4 and NH 3 gas mixture [2,3]. Until now, we have reported that moisture-resistive SiN x films can be formed at 80 -C by adding hydrogen to the source gases [4].…”
Section: Introductionmentioning
confidence: 99%
“…Deposition rate, 16BHF etch rate, refractive index and N/Si ratio for SiN x films prepared at various substrate temperatures. Flow rates of SiH 4 , NH3 and H 2 were fixed to 10 sccm, 20 sccm and 400 sccm, respectively.…”
mentioning
confidence: 99%